A Rare Case of Pneumopericardium in the Setting of Tuberculous Constrictive Pericarditis - Lauro L. Abrahan IV; Stephanie Martha O. Obillos; Jaime Alfonso M. Aherrera; Jose Donato A. Magno; Celia Catherine C. Uy-Agbayani; Ulysses King G. Gopez; Jobelle Joyce Anne R. Baldonado (Case Reports in Cardiology)
A 28-year-old Filipino male was admitted due to high-grade fevers and dyspnea on a background of chronic cough and weight loss. Due to clinical and echocardiographic signs of cardiac tamponade, emergency pericardiocentesis was performed on his first hospital day. Five days after, chest radiographs showed new pockets of radiolucency within the cardiac shadow, indicative of pneumopericardium. On repeat echo, air microbubbles admixed with loculated effusion were visualized in the anterior pericardial space. Constrictive physiology was also supported by a thickened pericardium, septal bounce, exaggerated respiratory variation in AV valve inflow, and IVC plethora. A chest CT scan confirmed the presence of an air-fluid level within the pericardial sac. The patient was started on a quadruple antituberculosis regimen and IV piperacillin-tazobactam to cover for superimposed acute bacterial pericarditis. Pericardiectomy was performed as definitive management, with stripped pericardium measuring 5–7 mm thick and caseous material extracted from the pericardial sac. Histopathology was consistent with tuberculosis. This report highlights pneumopericardium as a rare complication of pericardiocentesis. We focused on the utility of echocardiography for diagnosing and monitoring this condition on a background of tuberculous constrictive pericarditis, ultimately convincing us that pericardiectomy was necessary, instead of the usual conservative measures for pneumopericardium.